MASALAH-MASALAH DALAM KESEHATAN JIWA - Yohanes Firmansyah; Gunawan Widjaja (Cross-border, 2022)
In the modern era, mental health problems are in the spotlight in addition to the physical problems experienced by humans. There are many cases from a social and legal perspective that involve mental health issues. The purpose of this study is to describe legal and health issues from mental health issues. This research is a descriptive-analytical-explorative research with an approach in the form of a study of legislation (secondary data and primary – tertiary legal materials). The results of this study reveal that the 2014 Mental Health Law is the legal umbrella for mental health services in Indonesia, with continued implementation in the form of Minister of Health Regulation No. 75 of 2019 concerning Health Crisis Handling. In the Minister of Health Regulation there are regulations on mental health services in health facilities, especially Puskesmas, as well as integration with the formation of a national drug formulary that includes mental drugs in the list of mandatory drugs. On the other hand, the issue of mental health also mentions the existence of human rights of people with mental health, such as the issue of shackles, criminal acts of shackles, and the existence of special standards in handling cases where the defendant is a person with a mental disorder. The conclusion in this study is that the legal umbrella for mental health in Indonesia already exists, but its implementation in the field still requires further socialization so that its application can be evenly distributed throughout Indonesia.